Physicochemical and microbiological characteristics of minimally processed and stored pumpkin (Cucurbita moschata Poir.) (Research, Society and Development, 2024)
Pumpkin is one of the main vegetables used in human consumption, however, the rusticity of the fruit's skin and the excess of seeds are characteristics that reduce its commercialization, considering that there is a growing demand for foods that provide practicality and nutritional quality. Minimal processing of vegetables combined with conservation techniques is essential for maintaining the physical-chemical and microbiological quality of the food. Therefore, the objective of this work was to analyze the feasibility of minimal processing combined with blanching and freezing, as a way of preserving the alligator pumpkin (Cucurbita moschata). The experimental design used was completely randomized (DIC) in a 2x5+2 factorial scheme, consisting of two controls, (T1) = pumpkins with blanching and (T2) = pumpkins without blanching, both without freezing and two treatments (T3= blanching and freezing between (-18 ºC to -26 ºC) and T4= only freezing between (-18 ºC to -26 ºC) and five evaluation times (0, 5, 10, 15 and 20 days) of storage. Physical analyzes were carried out -chemistry of moisture, soluble solids, pH, titratable acidity, ascorbic acid and microbiological analysis of thermotolerant coliforms. Significant differences were observed between the results of treatments T3 and T4 for all variables analyzed. Minimally processed pumpkin subjected to conservation methods blanching followed by freezing or just freezing for a period of 20 days of storage, presented better nutritional quality for consumption when compared to fresh pumpkin processed without conservation treatments.